Public-political development conditions for children’s literature in Lithuanian realism at the beginning of the twentieth century - Auryla, V. (Psichologija, 1962)
The article analyzes the two directions of Lithuania ideological approaches to children’s reading at the beginning of the 20th century regarding the Marxist-Leninist doctrine of the two cultures in every national cultural spirit. The clerical bourgeoisie, who had followed the czarist regime, promoted religiosity, blind obedience to the czar, and ruling class reading books, and they published clerical children’s literature. The liberal bourgeoisie, frightened by the growth of the revolutionary movement, was against a revolution. The liberal bourgeoisie were joined by some democrats and progressive intellectuals who were concerned with public education, actively participated in the country’s cultural life, and worked for the liberal press. G. Petkevičiūtė-Bitė, P. Mašiotas, J. Jablonskis, K. Vairas-Račkauskas, K. Skabeika, and others wrote about the education of children and children’s literature. Revolutionary Social Democrats (V. Mickevičius-Kapsukas, Z. Aleksa-Angarietis, etc.) demanded abolition of child labor, the introduction of universal children’s education, and education’s democratization. After an analysis of the social and political situation in the beginning of 20th century Lithuania, the article concluded that the leading Lithuanian authors depicting the tragic situation of children in the capitalist political system were influenced by the national liberation and social fight of the nation. J. Biliūnas, Žemaitė, Lazdynų Pelėda, L. Didžiulienė-Žmona, K. Jasiukaitis, V. Mickevičius-Kapsukas, J. Šepetys, J. Janonis, K. Stiklius, K. Lekeckas, and others portrayed Children’s life as oppressed and exploited by the bourgeoisie. Progressive ideas were reflected in M. Pečkauskaitė’s Šatrijos Ragana (Witch’s) story "The Light" and in the best stories of K. Sakalausko-Vanagėlis, P. Mašiotas M. Grigonis for children. A religious world view established itself in Lithuanian literature as, reflected in some moments of the class struggle at the beginning of 20th century. It was the beginning of a fierce fight with reactionary children’s writers and teachers who sought to tear away the children from the knowledge of the social realities of life, to educate them in the spirit of clericalism, apolitically, obedient to the bourgeoisie. Realistic Lithuanian children’s literature development conditions are analyzed on the basis of archival documents and other sources from the beginning of the 20th century.